MORAL VALUES AND THE ISSUES OF EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This work discusses the role of moral values in human life and highlights the importance of education in shaping them. Moral values are viewed as key factors that determine a person’s worldview, behavior, and cultural conduct in society. Education, in turn, is emphasized as the main tool for instilling these values in the younger generation. The paper also examines the role of family, educational institutions, and society in nurturing moral values, as well as the significance of traditions and customs. In addition, it reflects on the challenges and opportunities of strengthening young people’s moral and spiritual outlook in the context of globalization. The study concludes that an individual raised on the basis of moral values becomes the foundation for building a well-rounded and mature generation.